A Study of the prevalence of infection by hydatid cysts in sheep and goat carcasses in Hama National Slaughterhouse (Journal of Hama University, 2026)
Hydatid cysts are a prominent health and economic challenge in the livestock, especially in sheep and goats. Therefore, this study aimed to detect the prevalence of hydatid cysts in sheep and goat carcasses at Hama National Slaughterhouse. 32,531 sheep and goat carcasses were examined at Hama National Slaughterhouse over a full year. The results of the visual examination of sheep and goat carcasses when detecting the presence of hydatid cysts showed that 1262 sheep carcasses and 883 goat carcasses were infected with hydatid cysts, with a prevalence of 6.01% in sheep carcasses and 7.65% in goat carcasses. It was also found that the highest prevalence of hydatid cysts was in sheep and goat carcasses in the spring season, where the prevalence in sheep and goat carcasses reached 9.19% and 13.20%, respectively. The study showed that female sheep and goat carcasses had the highest prevalence of hydatid cysts compared to males, with the prevalence in females reaching 10.15% and 11.57% in sheep and goat carcasses, respectively. These results are an indication of a risk to animal health and public health as well.